High-Intensity Interval Training - health benefits and risks - literature review - Plizga, Jakub; Jaworski, Arkadiusz; Grajnert, Filip; Głuszczyk, Agnieszka; Surma, Alicja; Cecot, Jakub; Parfianowicz, Agnieszka; Zarzecki, Konrad; Mandryk, Miłosz; Holdun, Nazar (Quality in Sport, 2024)
High-Intensity Interval Training (HIIT) has become a prominent exercise modality known for its efficiency and effectiveness in improving various health outcomes. This review critically examines the positive and negative health aspects of HIIT, focusing on its impact on cardiovascular health, metabolic function, weight management, psychological well-being, and life expectancy. Evidence suggests that HIIT significantly enhances cardiovascular health by improving VO2 max, reducing blood pressure, and enhancing endothelial function. Metabolically, HIIT improves insulin sensitivity, glucose metabolism, and lipid profiles, while effectively reducing visceral fat and enhancing mitochondrial function. In terms of weight management, HIIT promotes fat loss and muscle maintenance, contributing to favorable body composition. Psychologically, HIIT has been shown to reduce symptoms of anxiety and depression, improve cognitive function, and enhance overall mental health. It has also a positive effect on chronic pain conditions. Emerging studies indicate that HIIT may reduce mortality risk and extend life expectancy by improving cardiovascular and metabolic health. Despite these benefits, HIIT also presents risks such as a higher incidence of musculoskeletal injuries, potential adverse cardiac events in high-risk individuals, and the risk of overtraining and burnout. Special populations, including older adults, children, adolescents, and individuals with chronic conditions, can benefit from HIIT, but modifications and precautions are necessary to ensure safety and effectiveness. The review underscores the importance of individualized HIIT program design, thorough assessment, and continuous monitoring to maximize benefits while minimizing risks. Future research should focus on long-term effects, optimal protocols for diverse populations, and personalized HIIT approaches to enhance safety and efficacy.